Ectopic Pregnancy in Non-Adnexal Abdominal Cavity: Is it an Acute Abdomen? - Sánchez, Morelos Adolfo García; González, Mireya De La Fuente; Tamayo, Ramón Armando Sánchez; Rodríguez, María Isabel Estrada; Estrella, Mara Luz Terán; Bonola, Yamileth Jiménez; Pazos, Mauricio Israel Flores (British Journal of Healthcare and Medical Research, 2022)
Ectopic pregnancy is a rare condition defined as a pregnancy where the oocyte implants anywhere outside the endometrial tissue of the uterus, but it is even more remotely rare, the ectopic pregnancy in non-adnexal abdominal cavity. The objective is to report a case and analysis of the literature. 27-year-old female patient, who comes to the emergency department. No history of importance. Emergency surgery was performed due to clinical data of acute abdomen and systemic inflammatory response, in the exploratory laparotomy; a partial salpingectomy and a right oophorectomy, are performed tumour and/or gestational sac is resected. The clinical picture does not correspond in most cases to the diagnosis, so ultrasound is the gold standard for it. The treatment will depend on the special characteristics of each case and the criteria or expertise of the surgeon, as well as the health infrastructure installed. The driving lines are diverse and it´s prognosis is unexpected. The imperative to have a treatment judgment, as urgent or scheduled, type of surgical approach, adjuvant or exclusive therapy with methotrexate in conservative management; or failing that, only close surveillance for full-term pregnancy. Concluding in a prognosis that allows strategically, decimating the morbidity and avoiding the mortality of the patient.